Upaya Penurunan Agresif Pada Anak Pra-Sekolah Dengan Social Skills Training Therapy - Nurul Mawaddah; Ike Prafita Sari; Siti Rachmah (MEDICA MAJAPAHIT, 2021)
Aggressive in children is one of the big social problem because it can be a tendency that can persist into adulthood. Social skills training Therapy is needed to improve the social skills of pre-school children in order to build and maintain a positive relationship with the surrounding environment. This study aims to determine the effectiveness of social skills trainning therapy for aggressive pre-school children. The research design was quasi-experimental pre-post test with control group. The sampling technique was proportionate stratified random sampling and found the number of respondents 24 children were divided into 2 groups, 12 children given therapy social skills training and 12 children as control. Data were collected before and after therapy and then compare the results between the two groups. Statistical analysis showed a decrease in the aggressive in the group receiving social skills training therapy were significantly higher (pvalue < 0.05) compared to the control group.